(untitled) (Bioagro, 2025)
One of the benefits of shade-grown coffee crops is litter deposition, which can improve nutrient cycling and increase organic matter in the soil. The objective of this study was to evaluate the contribution of tree species in the production and deposition of litter, as well as in the potential of nutrient cycling in a coffee crop. Litter samplings were carried out in the tree planting rows (TPR) and between tree planting rows (TPI). Four deposition points were sampled in the TPR and TPI, spaced apart at 1.5, 3.0, 4.5, and 6.0 m from the trunk of the trees (Anadenanthera falcata, Peltophorum dubium and Cassia grandis). Nine samplings were carried out between October 2016 and September 2017. Higher deposition occurred in May, August, and September, and it was higher in the TPR. The species that most contributed to the deposition were the coffee plants and C. grandis. The coffee crop showed the highest accumulation of nutrients owing to the higher deposition of litter and higher levels of N, K and Mg, while C. grandis was the forest species that concentrated most Ca and S. The influence of forest species on nutrient cycling is minimal, primarily due to the reduced contribution of litter compared to coffee trees.